Korelasi Gambaran Radiografi Toraks dengan Karakteristik Klinis Pasien Terkonfirmasi Covid-19 - Retno Ariza; Anse Diana Messah; Fransisca Sinaga; Alfi Wahyudi; Sandhy Arya Pratama; Itsna Annisa (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Novel Coronavirus 2019 or as known as COVID-19 is a new disease that caused of Severe Acute Respiarory Syndrome Coronavirus-2 (SARS-CoV-2) which found in Wuhan, China at the end of the year, 2019. Beside of the clinical characteristics based on mild until severed of the illness such as fever, cough, loss of smelling until decrease of lungs perfussion, another of physical examination is required such as Polymerase Chain Reaction (PCR) which can be a gold standard for COVID-19 examination and Chest X-ray examination. The purpose of this research is to determine the correlation between of chest x-ray imaging with clinical characteristic of COVID-19 patients in COVID-19 referral hospital of Bandar lampung on periode March 2020 – September 2020. The type of this research is descriptive analytics with cross sectional method. The technical of collecting the sample is purposive sampling. The analytical data that used is univariate to show the distribution of frequency of the patients and bivariate (used Sprearman) to show the correlate and the strength of the research in COVID-19 patients in COVID-19 referral hospital Bandar lampung on periode March 2020 – September 2020. The result showed the significant correlation between clinical characteristic of COVID-19 patients with chest x-ray imaging with the p-Value 0.00 (p < 0.01) and the correlation strength is 0.948 which mean there was a strongest correlation between of both variables and the score is shown the positive way that mean both of the variables is one way which affect each other. From the result of the research we can conclude that more severed the clinical characteristic from COVID-19 patients, so more worse of chest x-ray imaging can be found.